MENCEGAH BRAIN ROT: PEMBELAJARAN DENGAN MENGGUNAKAN MEDIA VIDEO YOUTUBE DALAM MENGUJI KEMAMPUAN ANALISIS PESERTA DIDIK - Deni Nasir Ahmad; Giry Marhento; Zakiah Fithah A’ini; Aulia Masruroh; Nurma Tambunan; Luluk Setyowati; Arum Sanjayanti (Postgraduate, University of Mataram, 2026)
The phenomenon of brain rot, or the decline in analytical thinking skills due to passive consumption of digital content, is a new challenge in modern education. This study aims to test whether YouTube video-based learning improves students' analytical skills compared to conventional learning. The term